2018
DOI: 10.1007/s12551-017-0383-2
|View full text |Cite
|
Sign up to set email alerts
|

Applications of functionalized nanomaterials in photodynamic therapy

Abstract: Specially designed functionalized nanomaterials such as superparamagnetic iron oxide, gold, quantum dots and up- and down-conversion lanthanide series nanoparticles have consistently and completely revolutionized the biomedical environment over the past few years due to their specially inferring properties, such as specific drug delivery, plasmonic effect, optical and imaging properties, therapeutic thermal energy productionand excellent irresistible cellular penetration. These properties have been used to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 171 publications
(264 reference statements)
0
21
0
3
Order By: Relevance
“…Developments in photosensitizers have led to the advancement of PDT. Fakayode et al [ 134 ] reported the evolvement of nanoparticle self-lighting PDT (NSLPDT). NSLPDT depends on the use of QD particles, which exhibit a sustained and controlled luminescent light release after excitation.…”
Section: Biomedical Applications Of Qdsmentioning
confidence: 99%
“…Developments in photosensitizers have led to the advancement of PDT. Fakayode et al [ 134 ] reported the evolvement of nanoparticle self-lighting PDT (NSLPDT). NSLPDT depends on the use of QD particles, which exhibit a sustained and controlled luminescent light release after excitation.…”
Section: Biomedical Applications Of Qdsmentioning
confidence: 99%
“…Quantum dots are classified as nanocrystals of semiconducting materials consisting of an inorganic core and an aqueous organic coated shell. In terms of medical applications, quantum dots have been utilized in a diagnostic capacity for fluorescence imaging of tissue as well as therapeutic delivery vehicles for protein or drugs [ 34 , 35 ]. Other chemicals may also be composited to create a layer particle: a magnetic diagnostic core with a therapeutic shell.…”
Section: Development Of Perinatal Therapies Using Engineered Nanommentioning
confidence: 99%
“…The overall efficiency of PDT depends on various factors including the choice of photosensitizer (PS), wavelength of the light, tumor location and recognition and uptake by tumor cells. Nanotechnology has been proposed to overcome these limitations of PDT . In literature, there are many types of multifunctional nanoparticles that have been studied for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the surface plasmon resonance (SPR) peak of the gold nanoparticles should be tuned far from the absorption peaks of the PS. Additionally, the size, shape and dispersibility of gold nanoparticles used in a specific study should show uniformity in order to avoid any undesired biological effects . As another nanotechnological approach, quantum dots (QDs) have been reported to improve the optical properties of new and existing therapeutic agents .…”
Section: Introductionmentioning
confidence: 99%